Neuropsychological and cognitive deficits in children with disruptive behaviour disorders - Shikwambana, Bob Thomas (University of Limpopo (Turfloop Campus), 2006)
Disruptive Behaviour Disorders are often associated with high rates of school drop outs, academic skills deficits and low achievement, drug abuse, low self esteem, depression, delinquency and incarceration. The main aim of the study was to establish whether children with DBDs are cognitively and/or neurologically impaired. The study investigated (1) whether children with DBDs show deficiencies in cognitive and motor functions and (2) whether gender and subtype influence cognitive and motor functions. Method: The sample of 137 children with DBDs (ADHD, ODD and CD) and those without a diagnosis of DBDs was drawn from children aged between 8 and 15 years. They were assessed using instruments that were selected to be measures of Executive Functions, cognitive functioning, and motor functions. The scores obtained from the administration of these measures were compared for significant differences between the DBD subtypes and a non-DBD control group as a possible function of gender. Results: The findings indicate that children with symptoms of DBDs performed poorer than the control group on all tests with the exception of the Digits backward. EF and motor impairments are associated with ADHD-C and ADHD-PI, and not with ADHD-HI, ODD and CD. Although among the DBDs, neuropsychological and cognitive impairments have been found to be severe in children with ADHD-PI and ADHD-C, the ADHD-C subtype showed qualitatively larger differences with the normal control group on most measures. There were no differences found between the genders in the performance on all tests that were administered. Conclusion Children of the ADHD-C and ADHD-PI subtypes are significantly more impaired on measures of Executive, cognitive and motor functions than those with ADHD-HI, ODD and CD and those without externalising disorders. However, the ADHD-C subtype found to be more severely impaired when compared with the ADHD-PI subtype.
Thesis (M.A. (Clinical Psychology) --University of Limpopo, 2007
Keywords: Neuropsychological deficits; Cognitive deficits; Disruptive behaviour disorders; 155.413; Neuropsychology -- South Africa; Behavior disorders in children -- South Africa; Clinical psychology